(untitled) (Proceeding of the International Conference on Arts and Humanities, 2018)
The two physical models, dancer and architecture coexist as an intertwined system of Hindu philosophy. Both dance and dancer function as a vehicle for divine invocation and are mirrored in the architectural surroundings. This paper attempts to illustrate the deeply seated connection between ancient south Indian dance and architecture so that we can see the symbiotic relationship of both of these arts and their mutual dependence in aesthetic expression. The Hindu philosophy of the cosmic man and its religious relationship with the Dravidian architecture of Tamil Nadu is the starting point of the discussion of south Indian aesthetics. The temple, as a setting for dance performances, and constructed based on the mandala, shares this quality of immersing its participants into a multi-sensory spatial experience.